Genetic characterization of almond (Prunus dulcis) cultivars and natural resources - Halász J.; Skola I.; Kodad O.; Ercisli S.; Ledbetter C.A.; Hegedüs A. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
This study was conducted to analyse the structure of molecular variation among Hungarian almond genotypes and to estimate the level of genetic diversity. A total of eighty-six almond samples originated from different geographical regions from Central Asia to California were evaluated using a set of 8 SSRs and 5 EST-SSR primer pairs. Amplification of DNA was successful for 11 of the 13 SSR loci. A mean value of 15.45 alleles per locus was found. Our data revealed a high level of genetic variability in most groups of samples. The highest number of alleles was detected in the Moroccan genotypes while the lowest number of alleles occurred in the group of self-compatible cultivars. All Hungarian cultivars and accessions were characterized by an average allele number of above 5. The correspondences between the genetic diversity and mating strategy highlight the role of the self-(in)compatibility system in shaping the genome of a fruit tree species.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)